Acculturative stress and cultural identity styles as predictors of psychosocial functioning in Hispanic Americans. (January 2021) - Ward, Colleen; Szabó, Ágnes; Schwartz, Seth J.; Meca, Alan
Abstract: We test acculturative stress, Hybrid (HIS) and Alternating (AIS) Identity Styles, and their interaction effects as predictors of psychosocial functioning over a 12-day period among Hispanic American university students. Participants completed measures of acculturative stress, HIS, AIS, and internalizing (anxiety and depression) and externalizing (social aggression and rule-breaking) symptoms on Day 1; on Day 12 they completed the symptom measures a second time. Structural equation modelling was used to examine the Day 1 effects of acculturative stress, cultural identity styles, and their interactions on Day 12 symptoms controlling for the Day 1 symptoms. We hypothesized that acculturative stress would predict more, and the HIS would predict fewer, symptoms and that the AIS would moderate the relationship between acculturative stress and symptoms over time. Results indicated that: (1) acculturative stress predicted an increase in internalizing symptoms; (2) the HIS predicted a decrease in internalizing and externalizing symptoms; and (3) the AIS attenuated the relationship between acculturative stress and externalizing symptoms. The results are discussed in relation to the distinctive features of internalizing and externalizing symptoms, and recommendations for future research are advanced.